From critique of economics to the primacy of social struggles in contemporary planning debates: A critique of selected technology-centered receptions of the Socialist Calculation Debate - Stojanović, Potjeh (Momentum Quarterly, 2022)
Whereas the economic socialist calculation debate contemporarily draws renewed interest under the impression of technological innovations, the current debate widely neglects feminist and class-centered critique of economics. Especially Morozov’s conception of digital socialism which he derives from a discussion of said debate is criticized in this article. His discussion of non-market institutions are characterized as market institutions in the neoclassical sense via a critical reflection of general equilibrium theory. Conventional assumptions about the independent rational actor enter Morozov’s institutions implicitly. Also, his focus on price and information neglects the (re-)productive dimension of the economy. Therefore, it tends to reproduce problems of general market equilibria. This technology-centered conception of socialist planning is contrasted with a conception centered around the collective practice of the institution of the assemblage in the Feminist Strike movement. Potential influences between emancipatory practice and theory of planning are discussed eventually.
Keywords: socialist calculation debate; digital socialism; general equilibrium theory; critical political economy; planning debate